Síntese de heterociclos via reações de ciclocondensação de a-etiloxalil e -pirazolil(alquil) b-dimetilaminoenonas com1,2- ou 1,3-Dinucleófilos - Fiss, Gabriela Fehn (2009)
Chemoselective synthesis of ethyl 4-pirimidinecarboxylates and/or ethyl 5-pirimidineoxalates via cyclocondensation reaction of b-dimethylaminoenones [R1C(=O)C(=CNMe2)C(=O)CO2Et, where R1 = Ph, 4-MeC6H4, 4-MeOC6H4, 4-BrC6H4, 4-ClC6H4, 4-FC6H4, 4-O2NC6H4, 2-thienyl, benzo[b]furan-2-yl and CF3] with NCN 1,3- dinucleophiles such as benzamidine hydrochloride or 1H-1-pyrazolyl-carboxamidine hydrochloride (50-86%); utilization of ethyl 4-pirimidinecarboxylates (when R1 = Ph, 4-MeOC6H4, 4-FC6H4 and 2-thienyl) in the cyclization reaction with hydrazine monohydrate, leading to 7,8-dihydropyrimido[4,5-d]pyridazin-8-ones (81-92%). In this work it was also studied the condensation reaction of (3,5-dimethyl-1H-1- pyrazolyl)alkylketones with N,N-dimethylformamide dimethylacetal, with the aim to obtain b-dimethylaminoenones [PhC(=O)C(=CNMe2)(3,5-dimethyl-1H-1-pyrazolyl), PhC(=O)C(=CNMe2)(3,5-dimethyl-1H-1-pyrazolylmethyl) and MeC(=O)C(=CNMe2)(3,5-dimethyl-1H-1-pyrazolyl)] (92-98%); and synthesis of 1,4 -biazoles via cyclocondensation reaction of b-dimethylaminoenones with different 1,2-dinucleophiles such as hydrazine monohydrate, terc-butylhydrazine hydrochloride,phenylhydrazine hydrochloride, carboxymethylhydrazine or hydroxylamine hydrochloride (50-80%). The X-ray diffraction technique was used in the elucidation of the stereochemistry of PhC(=O)C(=CNMe2)(3,5-dimethyl-1H-1-pyrazolylmethyl) and regiochemistry of the cyclocondensation reactions.